Asthma reviews: an essential part of good care. (1st November 2022) - Henry, Heather
Abstract : Asthma reviews are an essential part of long-term conditions management in general practice. An assessment of asthma control will help practice nurses to prioritise frequency and effort, but caution must be taken to not overlook those with poor control who do not seek help and/or do not adhere to treatment. Asthma reviews are an opportunity to assess, review and collaborate on clinical and self-management. Empathic communication and shared decision-making are key to relationship building.